Development of Entrepreneurial Character in Farmers Through Extension Activities - Sila, Maria Yenitriana; Keraf, Fransiskus Markus Pereto; Falo, Marsianus; Tabenu, Oktovianus; Kune, Simon Juan (Neolectura, 2024)
The research problem stems from the lack of entrepreneurial character in farming, due to the absence of routine extension activities. This study aims to identify the factors related to entrepreneurial character through red onion extension activities in Jak Village, Miomaffo Timur District, North Central Timor Regency. The data analysis model used in this study is Spearman Rank Correlation Test Analysis. The data collected includes both primary and secondary data. Data analysis uses Spearman rank correlation analysis to identify factors associated with entrepreneurial character through red onion extension activities in Jak Village, Miomaffo Timur District, North Central Timor Regency. The results of this study show that work ethic and responsibility, innovative behavior, and courage have a positive association with the level of participation in agricultural extension activities. This relationship is most prominent in aspects of seed selection, planting, as well as harvesting and post-harvest activities. These findings highlight the importance of considering the personal characteristics of farmers when designing and implementing effective agricultural extension programs.